Building and analysis of protein-protein interactions related to diabetes mellitus using support vector machine, biomedical text mining and network analysis - Vyas, Renu; Bapat, Sanket; Jain, Esha; Karthikeyan, Muthukumarasamy; Tambe, Sanjeev; Kulkarni, Bhaskar D. (Computational Biology and Chemistry, 2016)
In order to understand the molecular mechanism underlying any disease, knowledge about the interacting proteins in the disease pathway is essential. The number of revealed protein-protein interactions (PPI) is still very limited compared to the available protein sequences of different organisms. Experiment based high-throughput technologies though provide some data about these interactions, those are often fairly noisy. Computational techniques for predicting protein protein interactions therefore assume significance. 1296 binary fingerprints that encode a combination of structural and geometric properties were developed using the crystallographic data of 15,000 protein complexes in the pdb server. In a case study, these fingerprints were created for proteins implicated in the Type 2 diabetes mellitus disease. The fingerprints were input into a SVM based model for discriminating disease proteins from non disease proteins yielding a classification accuracy of 78.2% (AUC value of 0.78) on an external data set composed of proteins retrieved via text mining of diabetes related literature. A PPI network was constructed and analysed to explore new disease targets. The integrated approach exemplified here has a potential for identifying disease related proteins, functional annotation and other proteomics studies. (C) 2016 Elsevier Ltd. All rights reserved.

Novel shear thickening fluids possessing high shear rates using monodispersed silica nanoparticles and PEG - Chavan, Nayaku; Dhage, Atul; Wale, Apparav; Thorave, Asmita; Rajdeo, Kishor; Kamble, Sanjay; Ponrathnam, Surendra; Tambe, Sanjeev; Verma, Sanjeevkumar (Polymer Bulletin, 2023)
Higher shear rate possessing homogeneous shear thickening fluids were synthesized using monodispersed silica nanoparticles and polyethylene glycol (PEG). Novel homogeneous methodology was developed for the synthesis of shear thickening fluids using monodispersed silica nanoparticles and PEG. Shear rate of shear thickening fluids (STF) was determined using rheometer at room temperature. The normal shear rate was observed in the range of 100 to 1200 s(-1), whereas higher shear rate 2000 s(-1) was obtained using monodispersed silica nanoparticles, PEG and shear rate enhancer. Monodispersed silica nanoparticles were synthesized in a typical one-pot using modified Stober's method at room temperature. Precursors were used for the synthesis of monodispersed silica nanoparticles such as tetraethyl orthosilicate (TEOS), ethanol, deionized water and ammonia as catalyst. Particle size of monodispersed silica nanoparticles was in the range of 100-1200 nm, and particle size distribution was varied from 0.000 to 0.221. Synthesis of monodispersed silica nanoparticles was studied by various parameters, namely effect of TEOS concentration, grade of ethyl alcohol, ammonia concentration and water concentration. TEOS concentration effect shows particle size and particle size distribution increases with increase in concentration of TEOS. Even though concentration of TEOS was increased up to 5 times the observation was same for all particle sizes such as 100, 300 and 500 nm. Particularly in the case of 300 nm monodispersed silica nanoparticle synthesis, as TEOS concentration was increased from 1 to 5X (5 times) the particle size was increased from 331.7, 447.8, 497.0, 512.0 and 531.7 nm and particle size distribution was 0.005, 0.000, 0.006, 0.007 and 0.089, respectively. The effect of grade of ethyl alcohol illustrates that Indian rectified spirit shows almost similar results with respect to China make ethyl alcohol. Comparative study of China and Indian rectified spirit shows silica nanoparticle size was 174.6 and 174.2 nm, and particle size distribution was 0.065 and 0.071, respectively. Ammonia concentration effect explains particle size and particle size distribution increases with increase in concentration of ammonia. Water concentration effect shows particle size and particle size distribution increases with increase in concentration of ammonia. Comparative data of water concentration effect for 1316 and 1974 mL shows particle size were 321.7 and 488.0 nm, and particle size distribution was 0.083 and 0.05, respectively, under similar conditions. Morphological studies displayed the shape of the silica nanoparticles was spherical, monodispersed and isolated. A typical TEM image of monodispersed silica nanoparticles for 500 nm was observed with extremely low polydispersity, i.e., 0.000. It is very difficult to get such a type of excellent photograph of monodispersity by Stober's method particularly on large scale. Rheology study of homogeneous shear thickening fluids studied by varying the parameters such as composition of silica nanoparticles with PEG, effect of amount of solvent, effect of refluxing time, effect of additive with respect to the mol. wt. of PEG and effect of additive such as Tannin. All these parameters of STF explored with respect to the shear rate and shear viscosity. Effect of ethanol amount on STF demonstrates the shear rate increases with increase in amount of solvent. Effect of refluxing time on STF exhibits the shear rate increases with increase in refluxing time. Effect of composition based on 500 nm monodispersed silica nanoparticles and PEG 200 with respect to 60:40, 65:35 and 70:30 composition was studied and the results predict that shear rate increases with increase in silica percentage in composition, i.e., 118, 265 and 1200 s(-1) for 60:40, 65:35 and 70:30 composition, respectively, whereas maximum viscosity decreases with increase in silica content, i.e., 2.559, 1.420 and 1.200 Pa.s for 60:40, 65:35 and 70:30 composition, respectively. Effect of additive on shear rate and shear viscosity illustrates that shear rate decreases with increase in additive percentage in composition, whereas maximum viscosity increases with increase in additive content. Effect of additives on shear rate and shear viscosity was performed using 65:35 composition with respect to PEG 200 along with PEG 6000 shows shear rate was decreased from 142 to 6.42 s(-1) and maximum viscosity was increased from 56.1 to 571.0 Pa.s when the quantity of PEG 6000 was doubled. In general, additive decreases shear rate and increases shear viscosity (maximum). But effect of Tannin as an additive on 500 nm monodispersed silica nanoparticles with PEG 200 using 70:30 composition showed enormous increase in shear rate, i.e., 2000 s(-1). This is anomalous behavior of additive was observed.
Keywords: Monodispersed silica nanoparticles; Nanocomposite; Polyethylene glycol; Shear rate; Shear thickening fluid